Gaya Bahasa Penyiar Program Cipaganti Dalam Menarik Minat Pendengar - Indriani, Tita -; Sumadiria, AS Haris; Paryati, Paryati (Jurusan Ilmu Komunikasi, Fakultas Dakwah dan Komunikasi, UIN Sunan Gunung Djati Bandung, 2020)
This study aims to find out (1) the delivery language of the cipaganti program announcer (2) how the cipaganti program announcers set the timing to insert humor, (3) the way the cipaganti program announcer regulates articulation while broadcasting on Ardan Radio 105.9 FM. This research method uses descriptive qualitative study method with data collection techniques in the form of interviews, observations and literature review. The results of the study show as follows, First in terms of the language of broadcast delivery, the